Reversible errors - Turow, Scott (New York : Farrar, Straus, Giroux, 2002)
This suspenseful novel is about a vicious triple murder and the man condemned to die for it. Complicating the situation is that the judge who originally found the man guilty is only recently out of prison herself, having served time for taking bribes.
Keywords: Kindle County (Imaginary place) -- Fiction; Attorney and client -- Fiction; Death row inmates -- Fiction